Nitrous oxide emission mitigation from biological wastewater treatment – A review. (October 2022) - Lee, Yu-Jen; Lin, Bin-le; Lei, Zhongfang
Graphical abstract: Highlights: N2 O removal from wastewater can be realized using biological treatment. Mechanisms of biological N2 O formation and consumption are outlined. Bacterial strains capable of N2 O reduction is a current research focus. Research needs and prospects of biological N2 O removal/valorization are discussed. Economic analysis on biological N2 O removal from wastewater is needed. Abstract: Nitrous oxide (N2 O) emitted from wastewater treatment processes has emerged as a focal point for academic and practical research amidst pressing environmental issues. This review presents an updated view on the biological pathways for N2 O production and consumption in addition to the critical process factors affecting N2 O emission. The current research trends including the strain and reactor aspects were then outlined with discussions. Last but not least, the research needs were proposed. The holistic life cycle assessment needs to be performed to evaluate the technical and economic feasibility of the proposed mitigation strategies or recovery options. This review also provides the background information for the proposed future research prospects on N2 O mitigation and recovery technologies. As pointed out, dilution effects of the produced N2 O gas product would hinder its use as renewable energy; instead, its use as an effective oxidizing agent is proposed as a promising recovery option.